SPECIAL EDUCATION IN EJA CAMPO AND ITS FUNDAMENTAL ROLE - Fábio da Rocha Cabral, José (Revista Gênero e Interdisciplinaridade, 2023)
Faced with serious problems experienced today, we know that education comes from the past, from the time of the Jesuits, when they were in Brazilian lands, the term education was used, which aimed to show people an opportunity to acquire other different knowledge. After a long time Brazil has always talked about education, but it was only after the emergence of the federal constitution that there was an improvement in education and the purpose of the term Educational Law. Pertinent legislation emerged, such as the Law and Guidelines and the Basis of Education, such as the Statute of the Child and Adolescent, whose purpose and focus was to protect the rights enshrined in Brazilian legislation. Much has improved in relation to the right to education in Brazilian legislation and its guarantee, but there are still several comprehensive and visible problems that make it difficult to walk the concepts of society and education. We must allow society, education and citizenship to walk together and observe that the pedagogies existing today do not really bring a taste for education. The Constitutional guarantee of education in legislation does not advance, but a typified pedagogy that arouses curiosity in children and adolescents of all age groups and especially those still far from public policies.